Kompetensi Guru Pendidikan Agama Islam dalam Mengatasi Kesulitan Belajar Siswa Kelas XII di SMA Bosowa Bina Insani Bogor - Ajeng Pratiwi; Santi Lisnawati (Journal on Education, 2023)
Learning difficulties are a problem that is often found in the world of education in this case the teacher is obliged to help overcome the learning difficulties experienced by students. For this reason, teachers must have competence, this competence is useful for overcoming learning difficulties experienced by students. The purpose of this study was to determine the competence of Islamic Religious Education Teachers, to find out what are the learning difficulties of the students, to find out how to apply the competence of Islamic Religious Education Teachers and how the competence of Islamic Religious Education Teachers is. This type of research is a case study qualitative research with a field research approach. The data collection technique for this research uses observation, interview, and documentation techniques. Data analysis was carried out by collecting data, reducing data, displaying data, and concluding. Based on the results of the research conducted, it was found that the first competence of Islamic Religious Education Teachers was competent. The two types of learning difficulties experienced by students were in reading and memorizing Al-Qur'an material. The three efforts made by Islamic Religious Education Teachers in overcoming student learning difficulties, namely using the peer teaching method, asking for help from parents, and the matriculation program, the four implementation results from the competence of Islamic Religious Education Teachers have been implemented.